The antioxidant activity of natural diterpenes: theoretical insights. Issue 25 (16th April 2020) - Vo, Quan V.; Tam, Nguyen Minh; Hieu, Le Trung; Van Bay, Mai; Thong, Nguyen Minh; Le Huyen, Trinh; Hoa, Nguyen Thi; Mechler, Adam
Abstract : Diterpenes that were isolated from Crossopetalum gaumeri (Loes.) Lundell (Celastraceae) plants are reported to exhibit a range of biological activities, in particular as radical scavengers. Abstract : Diterpenes that were isolated from Crossopetalum gaumeri (Loes.) Lundell (Celastraceae) plants are reported to exhibit a range of biological activities, in particular as radical scavengers. Thus further insight into the antioxidant activity of diterpenes in physiological environments is much needed but not studied yet. In this study, the antioxidant activity of nine natural diterpenes was evaluated using kinetic and thermodynamic calculations. It was found that the sequential proton loss electron transfer (SPLET) mechanism is favored in polar environments, whereas formal hydrogen transfer (FHT) is the main pathway for the radical scavenging of these diterpenes in the gas phase as well as in lipid media. The rate constants for the HOO˙ radical scavenging of these compounds in the gas phase, polar and nonpolar solvents are in the range of 2.29 × 10 −2 to 4.58 × 10 7, 9.74 × 10 −3 to 1.67 × 10 8 and 3.54 × 10 −5 to 1.31 × 10 5 M −1 s −1, respectively. 7-Deoxynimbidiol (6 ), exhibits the highest HOO˙ radical scavenging with k overall = 1.69 × 10 8 M −1 s −1 and 9.10 × 10 4 M −1 s −1 in water and pentyl ethanoate solvents, respectively, that is about 1300 times higher than that of Trolox in polar environments. It is thus a promising natural antioxidant in physiological environments.